Revisiting amino acid analyses for bioadhesives including a direct comparison of tick attachment cement (Dermacentor marginatus) and barnacle cement (Lepas anatifera). (March 2021) - Engel, Benedikt; Suppan, Johannes; Nürnberger, Sylvia; Power, Anne Marie; Marchetti-Deschmann, Martina
Abstract: With respect to potential applications in healthcare, pharmacy, the bonding industry, and cosmetics, biological adhesives produced from various animals are of high interest. A large number of species in the family Ixodidae produce an adhesive substance called attachment cement. This study focuses on the detailed investigation of the amino acid composition of the attachment cement from ticks ( Dermacentor marginatus ) and comparison with cement samples from barnacles ( Lepas anatifera ). Strong emphasis was laid on sample preparation of both types of cement and included the complete hydrolysis of proteins under either basic or acidic conditions. Stability of propyl chloroformate derivatives of the amino acids were measured by liquid chromatography electrospray ionisation tandem mass spectrometry (LC-ESI-MS/MS) and gas chromatography electron ionisation tandem mass spectrometry (GC-EI-MS/MS) and were validated in terms of reproducibility and precision of analyses using NIST certified amino acid as well as protein standards. For the majority of the amino acids analytically valid recovery rates between 86 and 111% were achieved using GC-EI-MS/MS analysis after acidic hydrolysis. The method was applied for direct comparison of two biological glue systems, tick and barnacle cement. An outstandingly high content of glycine was present in the tick attachment cement; as were significant concentrations of leucine, serine and proline. In contrast, high levels of leucine, serine, aspartic acid/asparagine, glycine, glutamic acid/glutamine, alanine and valine were determined for barnacle cement. None of the samples showed the presence of 3, 4-dihydroxy-phenylalanine (DOPA), yet tick attachment cement exhibited significantly higher concentration levels of tyrosine, the precursor of DOPA. It can clearly be stated that published results for amino acid analysis of barnacle cement show significantly under-/overestimation for some amino acids. Distinct differences in amino acid presence and concentration were observed for the two bio-adhesives. Although both have cement-like properties the data implied that different attachment mechanisms are involved for each of the organisms.